2021
DOI: 10.1111/cpf.12728
|View full text |Cite
|
Sign up to set email alerts
|

Males with abdominal aortic aneurysm have reduced left ventricular systolic and diastolic function

Abstract: Abdominal aortic aneurysm (AAA) is a disease that predominantly affects elderly males. In developed countries, AAA is estimated to cause 1•3% of deaths in males aged 65-85 years (Sakalihasan et al., 2005).AAA is usually asymptomatic, only rarely producing clear symptoms.Rupture of the aneurysm is a life-threatening event, with a survival rate of only 10%-20% (Hultgren et al., 2016). However, even without rupture, AAA increases the risk of other major cardiovascular events, including chronic heart failure, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…Increased afterload of the heart has negative consequences on the systolic function. This is confirmed by the observation of Malm et al, that patients with AAA have significantly decreased systolic function assessed by global longitudinal strain and ejection fraction [48]. The time from the beginning of the pressure wave to the first systolic peak (CT1) defines the first phase of the systole, in which ventricles start to contract.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Increased afterload of the heart has negative consequences on the systolic function. This is confirmed by the observation of Malm et al, that patients with AAA have significantly decreased systolic function assessed by global longitudinal strain and ejection fraction [48]. The time from the beginning of the pressure wave to the first systolic peak (CT1) defines the first phase of the systole, in which ventricles start to contract.…”
Section: Discussionsupporting
confidence: 54%
“…The CT1 is dependent on the contractility of the left ventricle and the afterload. As has been shown by Malm et al global longitudinal strain (GLS), which is a surrogate marker of systolic function of the left ventricle is slightly decreased in patients with AAA when compared to a control group [48]. Thus, the shortening of the CT1 cannot be affected by the increased contractility of the left ventricle but is a result of changes in the afterload.…”
Section: Discussionmentioning
confidence: 87%
“…For example, the co-prevalence of AAA and thoracic aortic aneurysm is 10–30% [ 7 9 ]. Further, recent studies associated AAA with increased left-ventricular workload and faster ageing of the central arteries [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Quantitation calculation of BP for general aortic parts revealed that Emax was negatively associated with thrombus formation while E min was positively related. It has been reported that male AAA patients had reduced ventricular systolic and diastolic function ( Åström Malm et al, 2022 ). Our result indicated that for patients with CHD (both HFrEF and HFpEF) in clinical practice, we should pay more attention to their increased risk of thrombus formation after EVAR.…”
Section: Discussionmentioning
confidence: 99%